Children with special needs in music arts education programmes: challenges - Moreno, Davys (2021)
In order to contribute to Inclusive Education of children with Special Needs in Arts education programmes in Portugal, an Action-Research project started at the University of Aveiro in 2018. We intend to find solutions for children with motor disabilities due to Cerebral Palsy who enter in music Arts education programmes in the First Cycle of Basic Education, to develop their music potential and abilities through the use of Digital Technologies and Assistive Technologies. We used the Action Research and Content Analysis supported by Computer-assisted Qualitative Data Analysis Software webQDA platform throughout our study. We present what has been done so far: literature review, short training workshop and characterization of the child. With the compiled information it was determined that it is necessary to carry out an Intervention Programme in the Artistic School of the Conservatory of Music Calouste Gulbenkian, Aveiro. This includes a music teachers’ intensive Training Workshop focused on the use of Digital Technologies and Assistive Technology, to promote the inclusion of children with Special Needs in music Arts education programmes.